The P body protein LSm1 contributes to stimulation of hepatitis C virus translation, but not replication, by microRNA-122 - Roberts, Ashley P.E.; Doidge, Rachel; Tarr, Alexander W.; Jopling, Catherine L. (Oxford University Press, 2014)
The P body protein LSm1 stimulates translation and replication of hepatitis C virus (HCV). As the liver-specific microRNA-122 (miR-122) is required for HCV replication and is associated with P bodies, we investigated whether regulation of HCV by LSm1 involves miR-122. Here, we demonstrate that LSm1 contributes to activation of HCV internal ribosome entry site (IRES)-driven translation by miR-122. This role for LSm1 is specialized for miR-122 translation activation, as LSm1 depletion does not affect the repressive function of miR-122 at 3′ untranslated region (UTR) sites, or miR-122–mediated cleavage at a perfectly complementary site. We find that LSm1 does not influence recruitment of the microRNA (miRNA)-induced silencing complex to the HCV 5′UTR, implying that it regulates miR-122 function subsequent to target binding. In contrast to the interplay between miR-122 and LSm1 in translation, we find that LSm1 is not required for miR-122 to stimulate HCV replication, suggesting that miR-122 regulation of HCV translation and replication have different requirements. For the first time, we have identified a protein factor that specifically contributes to activation of HCV IRES-driven translation by miR-122, but not to other activities of the miRNA. Our results enhance understanding of the mechanisms by which miR-122 and LSm1 regulate HCV.